Alignment of the Incisura Fibularis with the Lateral Border of the Talus on Mortise View Radiographs in Ankle Injuries. Issue 4 (16th October 2019) - Tseng, Jasper; Stewart, Gary W.; Kane, Steven; Mason, Bonnie S.
Category: Ankle, Trauma Introduction/Purpose: Diagnoses of ankle injuries utilize plain radiographs in three views: anteroposterior (AP), lateral, and mortise. Mortise view has greater sensitivity and accuracy in assessment of the distal tibiofibular syndesmosis through visualization of the mortise clear space. Current radiologic diagnostic parameters, like medial tibiotalar clear space and tibiofibular clear space, are inconsistent and unreliable because no consensus exists to measure these parameters. However, the incisura fibularis (IF) is a consistent landmark in assessing syndesmotic stability. We believe that in ankles without fracture, dislocation, or syndesmotic disruption, the IF aligns with the lateral border of the talus when observed on mortise view radiographs. This study seeks to determine a novel, more reliable radiologic parameter in diagnosis of the ankle mortise by evaluating this alignment. Methods: We retrospectively reviewed adult patient charts from 2012-2017 and selected 100 mortise radiographs: 23 bimalleolar fractures, 14 trimalleolar fractures, 13 fibular fractures, and 50 that were negative for fracture, dislocation, and syndesmotic disruption. We analyzed preoperative radiographs (after closed reduction, if displacement occurred) and postoperative radiographs at least 3 months after open reduction/internal fixation. Mechanism of injury, laterality of radiograph, and gender of patient were not considered in this sample. We evaluated the IF and talus alignment by drawing a line from the proximal IF, through the inferior tibia, to the lateral border of the talus (IFT line in Figure 1). We considered alignments < 1 mm from our IFT line to have mortise congruence since mortise widening >/= 1 mm can decrease contact area of the tibiotalar joint and cause instability. Chi-squared analysis compared non- fracture radiographs to pre- and postoperative fracture radiographs to determine significance with p < 0.05. Results: Among radiographs without fracture, dislocation, and syndesmotic disruption, 46/50 showed alignment < 1 mm from the IFT line. 14/50 preoperative radiographs had alignment < 1 mm from the IFT line: 2 bimalleolar fractures, 4 trimalleolar fractures, and 8 fibular fractures. 43/50 postoperative radiographs had alignment < 1 mm from the IFT line: 19 bimalleolar fractures, 13 trimalleolar fractures, and 11 fibular fractures. Chi-squared analysis determined statistical significance in comparison of non-fracture radiographs with preoperative radiographs by chi-squared statistic = 42.6667 and p < 0.00001. Chi-squared test showed no significance (p > 0.05) in comparison of non- fracture radiographs with postoperative fracture radiographs by chi-squared statistic = 0.9193 and p = 0.337657. Chi-squared test did not show significance among the different types of fractures. Conclusion: We implemented a novel approach to determine a more reliable radiologic parameter in evaluation of the ankle mortise by assessment of the alignment of the IF with the lateral border of the talus on mortise view radiographs. Radiographs without fracture, dislocation, or syndesmotic disruption have alignment < 1 mm from the IFT line, which suggests mortise congruence. Alignment >/= 1 mm may indicate mortise incongruence, distal tibiofibular syndesmotic instability, and talar shift. We conclude that the IFT line can be utilized to appraise the ankle mortise in distal tibiofibular syndesmotic injuries on mortise view radiographs.